2022
DOI: 10.1186/s13020-022-00666-9
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal and edible plants in the treatment of dyslipidemia: advances and prospects

Abstract: Dyslipidemia is an independent risk factor of cardiovascular diseases (CVDs), which lead to the high mortality, disability, and medical expenses in the worldwide. Based on the previous researches, the improvement of dyslipidemia could efficiently prevent the occurrence and progress of cardiovascular diseases. Medicinal and edible plants (MEPs) are the characteristics of Chinese medicine, and could be employed for the disease treatment and health care mostly due to their homology of medicine and food. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 201 publications
1
7
0
Order By: Relevance
“…In recent years, the prevalence of dyslipidemia in the Chinese population has been increasing, and dyslipidemia is one of the important independent risk factors for the development of cardiovascular diseases such as coronary heart disease and atherosclerosis [13,14]. The results of this study indicated that the detection rate of dyslipidemia in the elderly was 45.9%, and the prevalence of dyslipidemia in the Chinese population aged 60 years and older was 45.7% in a study by Li et al [14], consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the prevalence of dyslipidemia in the Chinese population has been increasing, and dyslipidemia is one of the important independent risk factors for the development of cardiovascular diseases such as coronary heart disease and atherosclerosis [13,14]. The results of this study indicated that the detection rate of dyslipidemia in the elderly was 45.9%, and the prevalence of dyslipidemia in the Chinese population aged 60 years and older was 45.7% in a study by Li et al [14], consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the exploration for new products to prevent or treat MDs is of high and continued interest. In the last decade, scientific researchers turned their attention to phytochemicals as effective, safe and low-cost natural bioactive compounds for MD treatment [15][16][17][18]. Phytochemicals such as polyphenols, alkaloids and terpenoids have good antioxidative activity and antiinflammatory effects, due to their ability to bind free radicals with their functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…), mulberry (Morus alba L.) leaf, and He-Shou-Wu (Polygonum multiflorum Thunb.) have been applied as healthcare food for fat reduction and weight loss (Gong et al, 2020;Y. Hu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…), mulberry ( Morus alba L.) leaf, and He‐Shou‐Wu ( Polygonum multiflorum Thunb.) have been applied as healthcare food for fat reduction and weight loss (Gong et al., 2020; Y. Hu et al., 2022). However, the specific mechanism of their anti‐obesity effects from the perspective of adipose browning remains unclear.…”
Section: Introductionmentioning
confidence: 99%